The Formation of Voting Behaviour Explained by Voting for Anti-European Parties (Fields, 2018)
The Brexit referendum and the last presidential election in the USA are just two examples of recent vote results that have been wrongly predicted. This research paper aims to identify the formation of voting behaviour to revaluate the necessary factors and variables in the correct and scientific prediction and analysis of voting behaviour. More specifically, this paper chose anti-European voting behaviour in Germany, which is also a current European-wide societal phenomenon, to analyse and explain the formation of general voting behaviour in detail. Many researchers, including Goodwin and Heath (2016), analysed the quality of existing polling methodology to explain the incorrect prediction of the Brexit result. This research forms a new approach towards the identification of voting behaviour by including more variables than usual. In collaboration with YouGov Deutschland GmbH, a strategic sample of the German population of 993 participants was formed. Participants were asked questions relating to individual differences, political ideology, attitudes towards daily political topics and socio-demographic factors. Voters who voted for the AfD, the main anti-European party in Germany, were more likely to be in some form of relationship, were more likely to be male, and over-represented the age group 40–49. Finally, voters voted for the AfD because the party engaged with political topics in a way that no other party did. This research is somewhat limited because the questionnaire focused on voters voting for the AfD. Furthermore, quantitative research can only identify and analyse individual human behaviour to a certain extent, whereas qualitative data, which this research lacks, can potentially help to identify voting behaviour. Relevant and important factors such as political ideology and individual differences, which are included here, but are usually not part of political research, must play a role in the future identification of voting behaviour.